EFFECTS OF CIVIC SKILLS AND VALUE CLARIFICATION TRAINING ON MORAL REASONING AMONG SECONDARY SCHOOL STUDENTS IN IBADAN METROPOLIS, NIGERIA (2016)
Moral reasoning is a constellation of beliefs, values and underlying objective judgements about the rightness or wrongness of beliefs and acts. Moral reasoning among secondary school students poses a major concern in the Nigerian society. While there are several survey studies on sociological determinants of moral reasoning among secondary school students, studies on psychological interventions to enhance moral reasoning are sparse. This study, therefore, determined the effects of civic skills training (CST) and value clarification training (VCT) on moral reasoning among secondary school students in Ibadan metropolis. The study examined the moderating roles of self-concept and gender on moral reasoning. Lawrence Kholberg’s Theory of moral reasoning provided the framework, while pre-testpost- test-control group experimental design with a 3x2x2 factorial design was adopted. Multi-stage sampling technique was used to select 118 participants from three randomly selected public senior secondary schools, which are known to have rampant cases of immorality. The students consisted of 71 males and 47 females with the age range of 13 to 19 years. The schools’ statutory records (Punishment Books) were used to screen students with frequent moral problems. The students were assigned to two treatment groups (Civic Skills and Value-clarification Training) and a control group. The treatment sessions lasted ten weeks. The two instruments used were: Moral Self-Concept (α = 0.75) and Moral Reasoning (α = 0.78) scales. Data were subjected to percentage, analysis of Covariance and Scheffe post-hoc at 0.05 level of significance. Secondary school students in Ibadan metropolis engage in cheating, fraud, drug addiction, rape, kidnapping and cultism. These negative behaviours are antithetical to moral reasoning. The prevalence of immoral behaviours among the participants was: truancy (81.0%), stealing (72.1%), examination malpractices (64.7%), bullying (63.7%) and pre-marital sex (56.9%). There was a significant main effect of treatments on moral reasoning of the participants (F2,104 = 2.85, 2 = 0.03). Students treated with civic skills training (CST) improved significantly ( ̅ = 101.85) than those treated with VCT ( ̅ = 95.74), while the control group mean value was 85.16. Gender had significant main effect on moral reasoning of the students (F1,104 = 7.303, 2 = 0.07); females ( ̅ = 101.74) benefitted more than males ( ̅ =89.18). There was no significant main effect of self-concept on moral reasoning of the students. There were no significant two-way interaction effect and three-way effect of treatment, gender and self-concept on moral reasoning of students. Civic skills training was more effective in enhancing the moral reasoning of secondary school students in Ibadan metropolis with females benefiting more than males. Educational stakeholders, especially counselling and educational psychologists should adopt Civic Skills and Value Clarification Training in boosting moral reasoning among secondary school student